On‐chip addressable Schottky‐on‐heterojunction light‐emitting diode arrays on AlGaN/GaN‐on‐Si platform. Issue 5 (17th February 2016) - Tang, Xi; Li, Baikui; Lu, Yunyou; Chen, Kevin J.
Abstract: In this work, the Schottky‐on‐heterojunction light‐emitting diodes (SoH‐LED) are monolithically integrated with the AlGaN/GaN high‐electron‐mobility transistors (HEMT) on an AlGaN/GaN‐on‐Si platform commonly used for GaN lateral electronic devices. The on‐chip electro‐optic modulation is realized in a single device fabricated using HEMT‐compatible process. Also, SoH‐LED arrays are fabricated to demonstrate the on‐chip addressable functionality with each SoH‐LED pixel in the array individually controlled by the integrated HEMT. High‐resolution micro‐scale SoH‐LED seven‐segment displays are demonstrated to show the potential of using SoH‐LEDs as a robust alternative for micro flat‐panel displays. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)